ANALISIS PERTIMBANGAN HAKIM MENGENAI “SIFAT KEDERMAWANAN” SEBAGAI ALASAN PEMOTONGAN MASA HUKUMAN KASUS KORUPSI (STUDI PUTUSAN MAHKAMAH AGUNG NOMOR: 237 PK/PID.SUS/2020) - Ovaldo Noor Hakim; Rugun Romaida Hutabarat (Jurnal Hukum Adigama, 2022)
Indonesia is a country based on law, its laws stand on everything. Although there have been many laws made in Indonesia, it is still felt that it is not optimal in granting a punishment against lawbreakers. Judges are the last bull for people looking for a ray of justice. However, judges sometimes give a sentence based on their conscience which can be both advantageous and disadvantageous for some parties. Currently, Indonesia does not have a punishment guideline for judges to decide on violators of the law, therefore it is important that judges have a punishment guideline for offenders, the purpose of this guideline is to reduce disparity and to achieve a higher standard of punishmentThe purpose of the law itself is to give justice to anyone. If the guidelines for conviction in Indonesia are born or present, there will be a decrease in legal disparity or legal differences with the same case and of course will provide a law that matches the criminal conduct committed by the legal subjects.